Accounting for changes in automobile gasoline consumption in Japan: 2000-2007 - Shigemi Kagawa; Yuriko Goto; Sangwon Suh; Keisuke Nansai; Yuki Kudoh (Journal of Economic Structures, 2012)
This paper analyzes gasoline consumption in Japan for the period 2000- 2007 using the index decomposition analysis (IDA). The changes in gasoline con- sumption in Japan were attributed to five factors: (1) change in the annual average driving distance of new and vintage cars, (2) change in the market share of new pas- senger cars, (3) change in the total number of new passenger cars, (4) change in the fuel economy of new passenger cars, and (5) change in the stock of vintage cars. We used the IDA results to estimate the economy-wide direct rebound effect, where im- proved fuel mileage causes additional travel. We found that the total gasoline saved by shifting from vintage ordinary passenger cars to both new kei passenger cars and new hybrid cars during fiscal 2006-2007 amounted to 395 ML, while about half of the gasoline savings from car replacement were lost by the direct rebound effects. The analysis shows that the direct rebound effect can be crucial in the effort of reducing overall gasoline consumption as well as household CO 2 emissions from passenger cars.
Keywords: Q41; Q43; 330; index decomposition analysis; gasoline consumption; rebound effect; automobiles